Perceived Organizational Hypocrisy and its Relations to, Conscientiousness among Private Hospital Workers - Kadhim Zrar Ahmed; Tanya Wasfe Abdwllah (Zanco Journal of Human Sciences, 2025)
Perceived institutional hypocrisy is one of the factors that affect employee behavior and the vitality of their conscience. Perceived institutional hypocrisy is the employees' perception of the existence of a contradiction. The research aims to study, identify the level of perceived institutional hypocrisy in a sample as a whole and according to its five dimensions and according to the gender and age variable, and identify the level of vitality of conscience in a sample as a whole. Also, according to the gender and age variable and the relationship between perceived institutional hypocrisy and vitality of conscience in a sample as a whole. The apparent validity and reliability of the two scales were achieved and applied to a random sample of (300). The research reached the results that the research sample suffers from a high level of institutional hypocrisy, and that there are statistically significant differences according to the gender variable in the dimensions and in favor of females so that they suffer more compared to males, and that the sample enjoys a low degree of vitality of conscience and there are differences between the sexes in the levels of vitality of conscience and in favor of females. No statistical differences appeared in vitality of conscience according to the age variable and the relationship between perceived institutional hypocrisy and vitality of conscience was weak